The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Interspeech 2018 2018
DOI: 10.21437/interspeech.2018-1233
|View full text |Cite
|
Sign up to set email alerts
|

Age-related Effects on Sensorimotor Control of Speech Production

Abstract: The current study investigates the effect of aging on the speech motor control, more specifically the labial and lingual system. We provide an acoustic and articulatory analysis comparing younger (20-30 years old) and older speakers (70-80 years old) of German, all of them recorded with electromagnetic articulography. We analyzed target words in contrastive focus condition.In the acoustic domain, target syllables were not prolonged in the productions of the older speakers. However, when looking at the articula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 15 publications
2
19
0
Order By: Relevance
“…There is also evidence that age affects the precision of speech motor control. In a study on German, Hermes et al (2018) found effects in speech similar to those reported for general motor control. Using 3D electromagnetic articulography, they tracked the movements of the lips and the tongue during the production of consonants and vowels in natural sentences, and found a slowing-down of articulatory movements that was accompanied by a change in the intragestural timing patterns of the primary constrictors during consonant and vowel production, revealing an asymmetry between acceleration and deceleration phases in the way that the deceleration phases were prolonged.…”
Section: Case Study 1: Ageingsupporting
confidence: 66%
See 3 more Smart Citations
“…There is also evidence that age affects the precision of speech motor control. In a study on German, Hermes et al (2018) found effects in speech similar to those reported for general motor control. Using 3D electromagnetic articulography, they tracked the movements of the lips and the tongue during the production of consonants and vowels in natural sentences, and found a slowing-down of articulatory movements that was accompanied by a change in the intragestural timing patterns of the primary constrictors during consonant and vowel production, revealing an asymmetry between acceleration and deceleration phases in the way that the deceleration phases were prolonged.…”
Section: Case Study 1: Ageingsupporting
confidence: 66%
“…Based upon the finding reported in Hermes et al (2018), we assume that ageing also affects the timing between gestures, i.e. it leaves a signature in the outcome of syllable-internal coordination patterns.…”
Section: Case Study 1: Ageingmentioning
confidence: 80%
See 2 more Smart Citations
“…Numerous studies have explored the acoustic, articulatory, and phonetic differences between standard and modified speech. Some of the conditions explored are Parkinsons [18], age [19], dyslexia [20], and ALS [21]. We add to this body of work by describing the phonetic mistakes that a production ASR system makes on a large collection of ALS audio.…”
Section: Related Workmentioning
confidence: 99%